Pendampingan Penulisan Bahan Ajar Berbasis Pendampingan Terbimbing di SDN 11 Ampang Kota Padang - Bustari, Bustari; Kustati, Martin; Amelia, Rezki; Kurnia, Asraf (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Writing high-quality teaching materials is an essential skill for teachers to enhance the effectiveness of learning. However, many teachers still face difficulties in developing teaching materials that are systematic, engaging, and aligned with the curriculum. This mentoring program aims to analyze the effectiveness of guided mentoring-based teaching material writing assistance at SDN 11 Ampang, Padang City. The mentoring process employs the Service Learning (SL) method, which includes several stages: needs identification, planning, implementation, as well as reflection and evaluation. The results of the mentoring indicate that guided mentoring-based assistance positively impacts the improvement of teachers’ competencies in preparing teaching materials. Teachers showed progress in technical skills, creativity, and understanding of curriculum standards. Therefore, this mentoring model is effective in enhancing teachers’ skills in producing higher-quality teaching materials. This approach can be recommended as a strategy for professional development of teachers in elementary schools.